Improving public health sector service delivery in the Free State, South Africa: development of a provincial intervention model - Benjamin Malakoane; James Christoffel Heunis; Perpetual Chikobvu; Nanteza Gladys Kigozi; Willem Hendrik Kruger (BMC Health Services Research, 2022)
Abstract Background Public health sector service delivery challenges leading to poor population health outcomes have been observed in the Free State province of South Africa for the past decade. A multi-method situation appraisal of the different functional domains revealed serious health system deficiencies and operational defects, notably fragmentation of healthcare programmes and frontline services, as well as challenges related to governance, accountability and human resources for health. It was therefore necessary to develop a system-wide intervention to comprehensively address defects in the operation of the public health system and its major components. Methods This study describes the development of the ‘Health Systems Governance & Accountability’ (HSGA) intervention model by the Free State Department of Health (FSDoH) in collaboration with the community and other stakeholders following a participatory action approach. Documented information collected during routine management processes were reviewed for this paper. Starting in March 2013, the development of the HSGA intervention model and the concomitant application of Kaplan and Norton’s (1992) Balanced Scorecard performance measurement tool was informed by the World Health Organization’s (2007) conceptual framework for health system strengthening and reform comprised of six health system ‘building blocks.’ The multiple and overlapping processes and actions to develop the intervention are described according to the four steps in Kaplan et al.’s (2013) systems approach to health systems strengthening: (i) problem identification, (ii) description, (iii) alteration and (iv) implementation. Results The finalisation of the HSGA intervention model before end-2013 was a prelude to the development of the FSDoH’s Strategic Transformation Plan 2015–2030. The HSGA intervention model was used as a tool to implement and integrate the Plan’s programmes moving forward with a consistent focus on the six building blocks for health systems strengthening and the all-important linkages between them. Conclusion The model was developed to address fragmentation and improve public health service delivery by the provincial health department. In January 2016, the intervention model became an official departmental policy, meaning that it was approved for implementation, compliance, monitoring and reporting, and became the guiding framework for health systems strengthening and transform in the Free State.